Pengembangan dan Implementasi Komunikasi Pendidikan Bencana Tsunami - Harnita, Pratiwi Cristin (Universitas Veteran Bangun Nusantara, 2021)
AbstractCommunication in disaster management uses a variety of media. In communication context, the media used as a channel for delivering messages that called the communication medium. This study aims to find the most effective disaster education communication based on a descriptive quantitative approach. Reserchers took samples aged 17-20 years old who had participated in disaster socialization activities that held by Meterorological, Climatological, and Geophysical Agency in Cilacap, Central Java, Indonesia and every respondent has had disaster experience. The number of research samples is 175 respondent. In the context of communication, the medium becomes important because it is a channel for delivering message. An import function of communication is how medium can delivered message to be undesrstood together. The fuction of communication is providing information, education and persuasion. It was found that varioys activities have beed carried out such as Goes To School, which is used to deliver messages used some communication medium like pocket books, animated video, and power point template. Fact findings related to the best communication medium were sozialization (face to face meetings), films, public service advertisements, and roleplays. Meanwhile, animated learning videos in class are not very popular. Keywords: disaster education communication, communication medium, communication function